2015
DOI: 10.1111/cdev.12342
|View full text |Cite
|
Sign up to set email alerts
|

Teacher–Child Interactions in Chile and Their Associations With Prekindergarten Outcomes

Abstract: Quality of teacher-child interactions is central to prekindergarten children's learning. In the United States, the quality of teacher-child interactions is commonly assessed using the teaching through interactions conceptual framework and an associ/ated observational tool, the Classroom Assessment Scoring System (CLASS). This study examined: (a) whether there was evidence supporting three distinctive domains of teacher-child interactions in Chile (construct validity) and (b) whether these domains predicted end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
2
30

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 222 publications
(206 citation statements)
references
References 43 publications
8
131
2
30
Order By: Relevance
“…Findings from a recent analysis of the Pelotas birth cohort in Brazil also demonstrated a doseresponse relationship between breastfeeding duration and increased intelligence, educational attainment, and income. (81,83) The positive effect of breastfeeding has been observed in one RCT in Belarus, where duration of total and exclusive breastfeeding was higher in the intervention group that received the baby-friendly hospital initiative, as well as performance in intelligence tests at 6.5 years. (84) A cohort analysis from South Africa found that exclusive breastfeeding was associated with fewer than average conduct disorders.…”
Section: Breastfeedingmentioning
confidence: 97%
“…Findings from a recent analysis of the Pelotas birth cohort in Brazil also demonstrated a doseresponse relationship between breastfeeding duration and increased intelligence, educational attainment, and income. (81,83) The positive effect of breastfeeding has been observed in one RCT in Belarus, where duration of total and exclusive breastfeeding was higher in the intervention group that received the baby-friendly hospital initiative, as well as performance in intelligence tests at 6.5 years. (84) A cohort analysis from South Africa found that exclusive breastfeeding was associated with fewer than average conduct disorders.…”
Section: Breastfeedingmentioning
confidence: 97%
“…in Latin America, Europe and the United States (Araujo et al, 2016 [90] ; Leyva et al, 2015 [91] ; [44] ; Pakarinen et al, 2010 [92] ). Although these relationships may vary from one domain of development to another, few studies show strong and consistent associations between the commonly studied dimensions (e.g.…”
Section: Links Between Staff-child Interactions and Children's Develomentioning
confidence: 99%
“…Los resultados mostrados por Hirokazu Yoshikawa en la Presentación Seminario Internacional de Educación Inicial 2, organizado por la Fundación Oportunidad (ver figura 3), mostró un gran aumento en el apoyo emocional (actividades El programa Un buen comienzo ha seguido desarrollándose y queda un registro de sus avances y resultados en diversos artículos Leyva et al, 2015;Leyva y Nolivos, 2015).…”
Section: Un Buen Comienzounclassified